Use of Reactive Distillation for Biodiesel Production: A Literature Survey - Muhammad Dani Supardan; Satriana Satriana (Jurnal Rekayasa Kimia & Lingkungan, 2006)
Biodiesel has been shown to be the best substitute for fossil-based fuels to its environmental advantages and renewable resource availability. There is a great demand for the commercialization of biodiesel production, which in turn calls for a technically and economically reactor technology. The production of biodiesel in existing batch and continuous-flow processes requires excess alcohol, typically 100%, over the stoichiometric molar requirement in order to drive the chemical reaction to completion. In this study, a novel reactor system using a reactive distillation (RD) technique was discussed for biodiesel production. RD is a chemical unit operation in which chemical reactions and separations occur simultaneously in one unit. It is an effective alternative to the classical combination of reactor and separation units especially when involving reversible or consecutive chemical reactions such as transesterication process in biodiesel production.